2008
DOI: 10.1053/j.gastro.2008.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Therapy for Liver Disease: Parameters Governing the Success of Using Bone Marrow Mesenchymal Stem Cells

Abstract: Background & Aims-Liver transplantation is the primary treatment for various end-stage hepatic diseases but is hindered by the lack of donor organs and by complications associated with rejection and immunosuppression. There is increasing evidence to suggest the bone marrow is a transplantable source of hepatic progenitors. We previously reported that multipotent bone marrow-derived mesenchymal stem cells differentiate into functional hepatocyte-like cells with almost 100% induction frequency under defined cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
353
1
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 423 publications
(379 citation statements)
references
References 50 publications
15
353
1
10
Order By: Relevance
“…This is interesting because, in addition to hepatic cells, bone marrow-derived hematopoietic and mesenchymal cells have already been examined in studies of the development of clinical CT protocols for liver regeneration. 27,28 The expression of hepatic markers in the characterized cell preparation overlapped with the expression of markers of adult human hepatic progenitor cells to some degree, as previously reported by other groups. 33,[40][41][42] Because of their availability, most studies of the isolation and in vitro propagation of adult liver progenitors have been performed with animal-derived cells, 40 and the majority of the isolation strategies for liver progenitors are based on the in vivo activation of the progenitor cell population 43 followed by the enzymatic digestion of tissue fragments and the selection of progenitors with a variety of techniques, such as centrifugation techniques, fluorescence-activated cell sorting, 46 and selective cell aggregate formation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This is interesting because, in addition to hepatic cells, bone marrow-derived hematopoietic and mesenchymal cells have already been examined in studies of the development of clinical CT protocols for liver regeneration. 27,28 The expression of hepatic markers in the characterized cell preparation overlapped with the expression of markers of adult human hepatic progenitor cells to some degree, as previously reported by other groups. 33,[40][41][42] Because of their availability, most studies of the isolation and in vitro propagation of adult liver progenitors have been performed with animal-derived cells, 40 and the majority of the isolation strategies for liver progenitors are based on the in vivo activation of the progenitor cell population 43 followed by the enzymatic digestion of tissue fragments and the selection of progenitors with a variety of techniques, such as centrifugation techniques, fluorescence-activated cell sorting, 46 and selective cell aggregate formation.…”
Section: Discussionsupporting
confidence: 79%
“…Although human FL tissue obtained during the first trimester mainly exhibits cells expressing hematopoietic [21][22][23][24] and endothelial cell markers, 25 the majority of the cells expressing hepatic markers appear in the early second trimester. 26 The presence of hematopoietic cells could be interesting because initial clinical studies of the transplantation of bone marrow-derived stem cell marker-positive cells 27 and bone marrow-derived mesenchymal stem cell (MSC) marker-expressing cells 28 have indicated that both hematopoietic and mesenchymal cell populations in the human FL may also be of interest for the development of liver CT therapy.…”
mentioning
confidence: 99%
“…The efficiency of MSC treatment in FHF patients was evidenced by the fact that FHF was rescued 4 weeks after MSC transplantation. 24 The rapid therapeutic effect indicates that the paracrine secretions of MSCs play a more important role than differentiation in MSC-mediated restoration of liver function. 25 IMDs including Crigler-Najjar syndrome 26 and primary systemic amyloidosis 27 have been successfully treated by stem cell transplantation in clinical trials.…”
Section: Therapeutic Mechanism Of Msc Transplantationmentioning
confidence: 99%
“…5 Recent work suggests that transplantation of native MSCs can alleviate liver injury through paracrine effects. 6 MSC-derived exosomes (MSC-Ex), membrane-enclosed vesicles found in MSC-conditioned medium (MSC-CM), have been reported to contribute to angiogenesis, neurite outgrowth, and skeletal muscle regeneration. [7][8][9] We previously demonstrated that hucMSCs and hucMSC-Ex could alleviate liver fibrosis, promote liver and renal injury repair, and improve wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] Antioxidant therapy has been considered for treatment of liver diseases, and previous work suggests that transplanted MSCs can restore liver function. 6,20 However, how MSC-Ex modulate oxidative stress in liver injury repair is unclear. Glutathione peroxidase 1 (GPX1), a critical human antioxidant, 21 detoxifies hydrogen peroxide and upregulates GPX1 activity to promote cell survival, but whether hucMSC-Exmediated delivery of GPX1 can restore liver function is unknown.…”
Section: Introductionmentioning
confidence: 99%